'Why did you not tell me?': perspectives of caregivers and children on the social environment surrounding child HIV disclosure in Kenya. (June 2015) - Vreeman, Rachel C.; Scanlon, Michael L.; Inui, Thomas S.; McAteer, Carole I.; Fischer, Lydia J.; McHenry, Megan S.; Marete, Irene; Nyandiko, Winstone M.
Abstract : Objective: We sought to better understand how social factors shape HIV disclosure to children from the perspective of caregivers and HIV-infected children in Kenya. Design: We conducted a qualitative study using focus group discussions (FGDs) to gain perspectives of caregivers and children on the social environment for HIV disclosure to children in western Kenya. FGDs were held with caregivers who had disclosed the HIV status to their child and those who had not, and with HIV-infected children who knew their HIV status. Methods: FGD transcripts were translated into English, transcribed, and analyzed using constant comparison, progressive coding, and triangulation to arrive at a contextualized understanding of social factors influencing HIV disclosure. Results: Sixty-one caregivers of HIV-infected children participated in eight FGDs, and 23 HIV-infected children participated in three FGDs. Decisions around disclosure were shaped by a complex social environment that included the caregiver–child dyad, family members, neighbors, friends, schools, churches, and media. Whether social actors demonstrated support or espoused negative beliefs influenced caregiver decisions to disclose. Caregivers reported that HIV-related stigma was prominent across these domains, including stereotypes associating HIV with sexual promiscuity, immorality, and death, which were tied to caregiver fears about disclosure. Children also recognized stigma as a barrier to disclosure, but were less specific about the social and cultural stereotypes cited by the caregivers. Conclusion: In this setting, caregivers and children described multiple actors who influenced disclosure, mostly due to stigmatizing beliefs about HIV. Better understanding the social factors impacting disclosure may improve the design of support services for children and caregivers.